Ancient Egyptian and Afroasiatic: rethinking the origins - Almansa-Villatoro, M. Victoria ca. 20./21. Jh.; Nigrelli, Silvia Štubňová ca. 20./21. Jh. (Languages of the ancient Near East, 2023)
"A collection of essays on ancient Egyptian, Semitic, and Afroasiatic linguistics, reexamining the position of ancient Egyptian in the Afroasiatic phylum and the closeness of its connections with languages that were spoken in Africa and the Ancient Near East"--